NG-STAR genotypes are associated with MDR in Neisseria gonorrhoeae isolates collected in 2017 in Shanghai. (12th November 2019) - Yang, Yijing; Yang, Yang; Martin, Irene; Dong, Yuan; Diao, Nannan; Wang, Ying; Demczuk, Walter; Gu, Weiming
Abstract: Objectives: To determine the association of Neisseria gonorrhoeae antimicrobial resistance and genotypes using N. gonorrhoeae sequence typing for antimicrobial resistance (NG-STAR). Methods: We characterized 124 N. gonorrhoeae isolates for their antimicrobial susceptibility profiles and NG-STAR ST characteristics using the guidelines of CLSI and EUCAST. The NG-STAR STs of seven loci were analysed. N. gonorrhoeae multiantigen sequence typing (NG-MAST) and MLST analysis was conducted in isolates with specific NG-STAR STs. Results: NG-STAR differentiated 124 N. gonorrhoeae isolates into 84 STs, of which 66 STs were novel to the NG-STAR database. NG-STAR ST-199, ST-348, ST-428, ST-497 and ST-1138 were the predominant STs. Three N. gonorrhoeae isolates with ceftriaxone and cefixime MICs ≥1.0 mg/L were grouped as NG-STAR ST-233. NG-STAR ST-202 isolates ( n =4) were associated with high azithromycin MICs and had an identical NG-MAST ST. The NG-STAR ST-348 group ( n =5) comprised more isolates with reduced susceptibility to cefixime ( n =4) than cefixime-susceptible isolates ( n =1). Conclusions: NG-STAR analysis differentiated N. gonorrhoeae isolates in settings with a high prevalence of antimicrobial resistance. Specific NG-STAR STs are associated with reduced susceptibility to ceftriaxone or cefixime and resistance to azithromycin in N. gonorrhoeae .